Fabrication and Properties of Silica Gel/Calcium Sulfate/Strontium-doped β-tricalcium Phosphate Composite Porous Scaffolds for Bone Tissue Engineering - QIN Xiao-su; HUANG Jie; GUO Hua-chao; YANG Ze-bin; CHEN Qing-hua; YAN Ting-ting (Cailiao gongcheng, 2018)
The calcium sulfate/strontium-doped β-tricalcium phosphate composite spherical pellets was fabricated, using the calcium sulfate/strontium-doped β-TCP as raw material, and through the stirring spray drying method, and then composite spherical pellets were combined with silica gel, porous silica gel/calcium sulfate/strontium-doped β-tricalcium phosphate scaffold was obtained by stacking aggregation method in the mould. The XRD, SEM and FT-IR, etc are employed to examine the chemical composition, composite morphology and structure characteristics, and the degradability, porosity, mechanical properties and cytotoxicity of the scaffolds materials were studied. The results reveal that the composite porous scaffolds have irregular pore structure with pore size between 0.2-1.0mm, and they have a large number of micropores on each of the composite spherical pellets, with the aperture between 50-200μm. Moreover, the porosity of the composite scaffolds is about 62%, which can meet the requirements of scaffolds for bone tissue engineering in porosity; the cytotoxicity tests show the composite scaffolds have no cytotoxic effect and it has good degradation. Therefore, it has good application prospect in bone tissue engineering of the bone defect repair of non-bearing site.